Organisation of industry and innovation dynamics - Tommaso Ciarli; Riccardo Leoncini; Sandro Montresor; Marco Valente (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2007)
The paper aims at investigating how the organization of a certain industry evolves once the competition among its firms, producing a 'com-plex' (i.e. non-modular) product, is modeled as the intertwining of innovative search and organizational change. In order to take the full roster of participants into account, and to retain the inner complexity of their decisions, a Pseudo–NK model is built–up in which a population of firms is called to match a technological frontier. By evolving along different stages of the sector's life-cycle, such a kind of technological calls for a trade–off between two strategies of cost–reduction through either outsourcing or technological search. Overall, the simulation results confirm previous literature as, for example, in the introductory stage of the industry life–cycle, marked by frequent and intense jumps of the technological frontier, firms need to vertically integrate in order to have higher chances to win the competition for a new standard. On the contrary, in the decline stage, in which the technological frontier almost stabilizes, deverticalization allows firms to better compete on costs. These results change if suppliers are allowed to innovate, as they are more likely to lock the market in sub–optimal configurations.
Keywords: 330